PENGARUH SERVANT LEADERSHIP DAN TRUST IN LEADERSHIP TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOUR - Perdana, I Komang Hady; Surya, Ida Bagus Ketut (E-Jurnal Manajemen; Vol 6 No 6 (2017), 2017)
The purpose of this study was to determine the effect of servant leadership and trust in leadership on organizational citizenship behavior in employees My Buss Denpasar. The population in this study are employees My Buss Denpasar Bali as many as 118 people. The method used in this research is census method. The data collection is done by distributing questionnaires using 5-point Likert scale to measure 12 question items. Analysis technique used is multiple linear regression analysis using SPSS 15:00 for windows. Analysis showed that servant leadership and significant positive effect partially on organizational citizenship behavior. Trust in leadership and significant positive effect partially on organizational citizenship behavior. Leaders must be mutual respect and recognize employee contributions to the team, improve the system of leadership by adopting an attitude of trust in leadership, integrity trustworthy employees and have competence trustworthy employees.
Keywords: servant leadership, trust in leadership, organizational citizenship behavior